Analysis of Motivations to Study English and Arabic - Yuyun Nailufar (Universitas Syiah Kuala, 2018)
This research was done to find out the major types of motivation used by students majoring in either English or in Arabic at the National Islamic University (UIN) Ar-Raniry in Banda Aceh when learning their chosen L2 language. Furthermore, this study tried to find out if there were similarities or differences in the main type of motivation used by students of each of these majors. The results of study were based on a questionairre survey and used qualitative research procedures to obtain the data. In collecting the data, the questionnaire was given to 30 English major students and also to 30 Arabic major students of UIN Ar-Raniry selected by random sampling. The results from this study showed that the English students at UIN Ar-Raniry were more influenced by high integrative motivation in choosing English as their major than by instrumental motivation. In addition, based on the questionnaire result, the students predominantly used integrative motivation in learning English, rather than instrumental motivation: This result was based on the mean score for instrumental motivation being lower than that for integrative motivation, viz: 3.15 vs 4.19. Similarly, the Arabic students at UIN Ar-Raniry were also predominantly influenced by integrative motivation to learn Arabic: This result was based on the mean score for instrumental motivation being lower than that for integrative motivation, viz: 3.09 vs 4.29. Based on these results, it can be concluded that both the English major students and the Arabic major students at UIN Ar-Raniry have similarities in the types of motivation that drives them to learn their chosen L2, target language. Students of both majors were predominantly driven by integrative motivation rather than by instrumental motivation.